PENGARUH CITRA MEREK DAN KUALITAS LAYANAN TERHADAP NIAT BELI ULANG MELALUI KEPUASAN KONSUMEN SILOKA TASIKMALAYA - Taupiq Apandi; Endang Tjahjaningsih (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Abstract: This study aims to examine and analyze the effect of brand image and service quality on repurchase intention through customer satisfaction at Siloka Coffee Shop Tasikmalaya. This research is expected to provide practical benefits for the management of Siloka Coffee Shop Tasikmalaya in formulating effective marketing and service strategies to enhance customer satisfaction and encourage repurchase intention. This study employs a quantitative research method with an explanatory research approach. The population of this study consists of all customers of Siloka Coffee Shop Tasikmalaya, with a sample of 101 respondents. Data were collected using a Likert-scale questionnaire, which was tested for validity and reliability. The data analysis technique used was multiple regression analysis and the Sobel test to examine both direct and indirect (mediating) effects among variables. The results of this study indicate that: (1) Brand image has a positive and significant effect on customer satisfaction; (2) Service quality has a positive and significant effect on customer satisfaction; (3) Brand image does not have a significant effect on repurchase intention; (4) Service quality has a positive and significant effect on repurchase intention; (5) Customer satisfaction has a positive and significant effect on repurchase intention; and (6) Customer satisfaction significantly mediates the effect of brand image and service quality on repurchase intention at Siloka Coffee Shop Tasikmalaya.